The global diffusion of environmental clubs: how pressure from importing countries supports the chemical industry's Responsible Care® program. (March 2020) - Holtmaat, Ellen Alexandra; Adolph, Christopher; Prakash, Aseem
Highlights: Trade helps diffuse positive environmental norms, especially when importing countries recognize such norms. Democracy encourages businesses to adopt pro-environmental policies. Business self-regulation is adopted when neighboring countries adopt similar codes. Responsible Care adoption is more likely when exporting to other countries whose national associations previously adopted RC. Abstract: Environmental clubs have proliferated across sectors and issue areas. We examine the diffusion of the chemical industry's Responsible Care® (RC) program. Much of the work on the diffusion of clubs has focused on the demand side: why firms join these clubs despite the costs of doing so. There is some work focusing on the supply side: why actors establish or create a new club. However, there is virtually no work examining why national-level industry associations decide to subscribe to an existing global environmental club in order to make it available to their members. Industry organizations in 17 lower and middle-income countries have joined RC, comprising 25 percent of RC members. We ask, in the context of developing countries, what motivates national associations to join RC? Drawing on an original dataset of RC global diffusion in 195 countries (1985–2017), we estimate a Cox proportional hazards model of the risk of joining RC. We find that RC adoption is more likely when a country exports chemicals to other countries that have joined RC (the California effect) and is unaffected by the total volume of its chemical trade. Thus, while exposure to global markets per se may not influence RC adoption, incentives change considerably when countries' key importers signal their support for these environmental practices. This is because importing firms often realize that because they have joined Responsible Care, NGOs and stakeholders expect them to demand that their overseas suppliers adopt the same sort of environmental policies and work place safety practices. In addition, peer pressure and learning matter: RC adoption is more likely when countries in close physical vicinity (e.g., within 500 miles) have joined the club. Finally, domestic factors play a role as well: both the level of democracy and the size of the economy encourage national associations to join RC.